2004
DOI: 10.1111/j.1399-302x.2004.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary IgA to cariogenic bacteria in HIV‐positive children and its correlation with caries prevalence and levels of cariogenic microorganisms

Abstract: The interrelationship of HIV infection, dental caries and mucosal immune responses remains controversial. In our study population of 40 HIV-infected and 40 healthy control children (ages 2-5 years) there was a significantly higher prevalence of dental caries in HIV-infected children (P<0.05). The extent of caries correlated with the severity of HIV disease. To determine whether the immunosuppression that ensues after HIV infection could contribute to the increased caries prevalence, the concentrations of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 31 publications
4
59
0
2
Order By: Relevance
“…However, as infection worsens, IgA concentration tends to decrease in AIDS patients. Such a fact is corroborated by Castro et al, 32 who observed that a group of more severely immunosuppressed patients had a low concentration of antibodies specific to cariogenic microorganisms. However, Wozniak et al 17 found no difference in the IgA concentration between patients presenting different levels of immunosuppression.…”
Section: Discussionsupporting
confidence: 66%
“…However, as infection worsens, IgA concentration tends to decrease in AIDS patients. Such a fact is corroborated by Castro et al, 32 who observed that a group of more severely immunosuppressed patients had a low concentration of antibodies specific to cariogenic microorganisms. However, Wozniak et al 17 found no difference in the IgA concentration between patients presenting different levels of immunosuppression.…”
Section: Discussionsupporting
confidence: 66%
“…These results, however, were not observed in the present study as the difference between active and inactive caries in our sample was not found to be statistically significant. On the other hand, Hicks et al (2000) and Castro et al (2004) have observed that children with low levels of CD4 had higher defs index. In the present study, the number of severely immunosuppressed patients was small, thus demonstrating that most children were immunologically healthy as their mean CD4 count was relatively high (19.85%).…”
Section: Discussionmentioning
confidence: 99%
“…local and systemic immune-deficiency) regarding HIV infection are involved (Madigan et al, 1996;Valdez et al, 1994;Castro et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations